On Political Islam in Palestine - Stepkin, E. A. (Vestnik MGIMO-Universiteta, 2015)
This article deals with analyzing the place and the political Islam occupies on the Palestinian territories. The author tries to prove that despite the “Arab spring” and growing popularity of Islamism in the neighbor Arab countries its popular support among Palestinians is low. The main reason for this is Israeli total control of political, economic and - partially - social processes taking place in the West Bank. Position of the officials in Ramallah who together with Tel-Aviv strictly contain spread of Islamism throughout the West Bank also has a strong suppressing effect. Central Palestinian leadership may be called one of the few secular political establishments that are still in power in the Arab countries. The main explanation for this is the desire to make a positive effect on the international community, which Palestine totally depends on in political and financial terms. Also one should keep in mind secular beliefs of the current political elite in Palestine. President Mahmoud Abbas with his counterparts from FATAH and PLO represent old type of Arab nationalist politicians, almost all of who were stripped from power after the beginning of “Arab spring” in 2011. Finally, Palestinian society itself still feels united by the idea of national liberation from the Israeli occupation. This helps Palestinians to put aside the issue of religious self-identification. According to the surveys, most of Palestinians still rank their national identity number while describing their identity, while religion comes only second (despite the strong stable tendency for growing Islamization of their views). The only Palestinian enclave where political Islam has gained ground is isolated Gaza Strip. However ruling there “Islamic Resistance Movement” (HAMAS), despite declared anti-Zionism and Islamism, in reality show pragmatic readiness for certain coordination of its actions with Israel and central government in Ramallah. Nowadays one can witness the deepening conflict within the Islamist camp - between HAMAS and more radical Salafists, who support “Islamic State” in Iraq and Syria. In the final end the fate of Political Islam in Palestine will depend on the success of Middle East peace process.